PENGARUH PEMBERIAN MINYAK IKAN TERHADAP KONSENTRASI ASAM LEMAK DAN GEJALA KLINIS MALARIA - Rasyid, Haerani; Suwandi, Danny (Lembaga Penelitian Universitas YARSI, 2007)
The aim of the study is to find out the effects of fish oil supplementation on fatty acids concentration (Eicosapentanoat Acid and Docosahexaenoat Acid), fever attacks and Dikke Drupple (DDR) interpretation of samples. This study was designed as ?A Randomized Double Blind Pretest and Post-test Controled Group?. Samples were divided into two groups, experiment group with fish oil suplementation (8% EPA, 35 DHA) and control group (placebo) for 8 weeks. This study was conducted in a malaria endemic, Kadaila village, subdistrict of Karossa, District of Mamuju in 2003. The result of the study showed significant increased concentration of EPA and DHA of the experiment group than the control group (p 0,05). The fever attack was significantly decreased (p 0,05) in experiment group than the control group, while DDR was not significantly different (p 0,05) between two groups.